PENGARUH SENAM MARYAM TERHADAP LAMA KALA II PADA IBU BERSALIN PRIMIGRAVIDA DI KLINIK MUTIARA MEDIKA RANGKASBITUNG KABUPATEN LEBAK - Tutik Iswanti; Nintinjri Husnida; Melly Halimatussa’adiah; Rasumawati (Politeknik Kesehatan Kementerian Kesehatan Banten, 2025)
Prolonged labor in the second stage is labor that lasts more than 2 hours in primigravidas and more than 1 hour in multigravidas. Factors causing a long labor process can be influenced by three things, namely energy, birth canal and fetus. The mother's own factors will be influenced by the mother's age, parity and readiness for childbirth. The duration of labor is not easy to determine precisely because the onset of labor is often unclear and subjective. In studies of women, whose labor began spontaneously, there was wide variation in the length of labor. Maryam gymnastics is a non-pharmacological therapy, where Maryam gymnastics can affect the psychology of mothers, especially pregnant women who experience psychological changes due to their pregnancy. The aim of the research was to determine the effect of Maryam exercise on the duration of the second stage of labor in primigravida mothers. The method used was Quasy Experiment with control group, the sample size was 66 respondents (33 intervention, 33 control), the sampling technique met the inclusion criteria. The intervention method that will be carried out is that pregnant women in the third trimester with a gestational age of 28-33 weeks will be intervened with maryam exercises three times a week for four weeks. After four weeks of intervention, the length of the second stage at the time of delivery will be seen with partograph. Data analysis with T Test, it was found that the average length of the second stage in the intervention group was 1.4 hours with a p value of 0.006. This statistically shows that there is an influence of maryam exercise on the length of the second stage